Integrated Nuclear-Renewable Energy System for Industrialization in West Nusa Tenggara Province, Indonesia: Economic, Potential Site, and Policy Recommendation - Hermawan, Erwan; Sudjadi, Usman (International Journal of Energy Economics and Policy, 2022)
Industrialization on renewable energy is needed to begin to avoid dependence on fossil fuels. West Nusa Tenggara (NTB) Province has the potential for the development of bioethanol which is integrated with the Small Modular Reactor (SMR) nuclear reactor. Through this study, the economics of sugar- ethanol plant and SMR reactors was calculated, as well as development schemes supported by policy recommendations will be presented. This study uses cash flow modelling from a sugar-ethanol plant and SMR to determine the economics of the project. The potential site is mapped by using scoring method to obtain the best location. The SMR reactor can operate with Internal Rate of Return (IRR) of 9%, Net Present Value (NPV) USD 2,325,347,181, and payback period 13 years. The sugar-ethanol plant has IRR of 12.6%, NPV 441,278,716, and payback period of 10 years. The appropriate locations for the construction of the SMR reactor are in Bima and Dompu districts, based on mapping analysis both locations have potential for future development.